Pengaruh Corporate Governance (Gc), Ukuran Perusahaan, Manajemen Laba dan Profitabilitas Terhadap Agresivitas Pajak - Purnowati, Della; Mujiyati, Mujiyati (Program Pascasarjana STIE Amkop Makassar, 2024)
This study aims to analyze the influence of corporate governance, company size, profit management, and profitability on tax aggressiveness. The type of data used is quantitative data with secondary data sources obtained from the financial statements and annual reports of mining sector companies listed on the IDX during the period 2020 – 2022. The population in this study is all mining sector companies listed on the Indonesia Stock Exchange for the period 2020-2022. The sample used in this study were companies that published financial statements and annual reports during 2020-2022. The sampling method is purposive sampling. The results of the study concluded that the variables independent commissioner, audit committee, institutional ownership, profit management have no effect on tax aggressiveness, while the variables of company size and profitability have an effect on tax aggressiveness. Keywords: Independent commissioner, audit committee, institutional ownership, profit management, company size, profitability, tax aggressiveness